Nursing care in HIV/AIDS in the palliative perspective: an integrative literature review (Research, Society and Development, 2022)
This study aims to analyze the care of professionals in the nursing area regarding comfort measures for patients with HIV/AIDS indicated for palliative care. This is an integrative literature review carried out by searching full articles from the last 10 years of publication (2012 to 2022) in the Virtual Health Library (BVS-BIREME), in the Latin American and Caribbean Literature databases in Health Sciences (LILACS) and the Scientific Electronic Library Online portal (SCIELO), regardless of language. The survey generated ten articles, listed in three distinct categories for discussion, namely: studies focusing on the clinical status of patients; studies focusing on conceptualized assistance in defining outcomes; studies focusing on the representativeness of the social portrait. Conclusion: after evaluating the clinical aspect of patients with HIV/AIDS from a palliative perspective, it was noticed that nursing professionals are concerned with physical and psychosocial relief, covering the inclusion of caregivers and family members in assistance with alternative services, designed in such a way as to minimize the pain and stress reported to the social environment, represented by the conduct in the general management of symptoms.